1994
DOI: 10.1111/j.1432-1033.1994.tb18690.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct analysis and significance of cardiolipin transverse distribution in mitochondrial inner membranes

Abstract: The distribution of cardiolipin across the inner mitochondrial membrane was directly determined by using the ability of the fluorescent dye 1 O-N-nonyl-3,6-bis(dimethylamino)acridine (10-N-nonyl acridine orange) to form dimers when it interacts with the diacidic phospholipid. Two independent methods were employed : (a) a spectrophotometric measurement of 10-N-nonyl acridine orange binding to isolated rat liver mitochondria, mitoplasts and inside-out submitochondrial particles, and (b) a flow-cytometric analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 51 publications
4
82
0
Order By: Relevance
“…We therefore tested the effects of the cardiolipin-binding dye nonyl acridine orange (NAO) on synuclein binding. NAO has a high affinity for cardiolipin, and binds via both electrostatic and hydrophobic interactions with a stoichiometry of 2 mol NAO/mol cardiolipin [57]. Based on phosphorous analysis, 1 mg/ml of total mitochondrial protein contained ~500 µM total phospholipid.…”
Section: Synuclein Binds To Purified Mitochondria At Low Phmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore tested the effects of the cardiolipin-binding dye nonyl acridine orange (NAO) on synuclein binding. NAO has a high affinity for cardiolipin, and binds via both electrostatic and hydrophobic interactions with a stoichiometry of 2 mol NAO/mol cardiolipin [57]. Based on phosphorous analysis, 1 mg/ml of total mitochondrial protein contained ~500 µM total phospholipid.…”
Section: Synuclein Binds To Purified Mitochondria At Low Phmentioning
confidence: 99%
“…Based on phosphorous analysis, 1 mg/ml of total mitochondrial protein contained ~500 µM total phospholipid. Using a spectrophotometric assay that measures binding of NAO to mitochondrial membranes [57], ~100 nmol NAO bound per mg total protein, which corresponds to ~50 nmol cardiolipin/mg protein, or ~10% cardiolipin/mitochondrial phospholipid. Using Syn1-102 in the mitochondrial binding reaction, NAO reduced synuclein binding to mitochondria at pH 6.0 in a concentration-dependent manner (Fig.…”
Section: Synuclein Binds To Purified Mitochondria At Low Phmentioning
confidence: 99%
“…As mentioned above, NAO binding to CL results in dimerization of the dye (15) in a stacking organization in which dye molecules are in close proximity. The emitted fluorescence of the complex shifts to red (emission peak at 640 nm for dimer and 525 nm for monomer) due to the metachromatic properties of acridine molecules (14). Experimental titration curves of CL with NAO in isolated rat liver mitochondria using flow cytometry showed that at an NAO concentration of about 100 to 200 nM, the intensities of the red and green fluorescent signals were almost the same (14).…”
Section: Microscopy Of Nao-stained E Coli Cells It Was Previouslymentioning
confidence: 99%
“…Interestingly, it was reported that 57% of total CL was present in the outer leaflets of inner membranes of isolated mitochondria. 30 Figure 1B, based on the knowledge of its structure, 36,37 proposes that subunit a of ATP synthase transfers H þ to Glu 58 at the center of subunit c. Then H þ through an Arg residue (R210 in E. coli 38 ) would pass to respiratory complexes, which, in turn, transfer them to the periplasmic side of the IMM. This putative pathway would be in line with the charged amino acids in subunit a.…”
Section: A Hmentioning
confidence: 99%
“…28 We may speculate that CL, a lipid molecule containing two hydrophobic domains, acts as a H þ shuttle at the centr of the membrane between subunit a of F o and ETC as tentatively depicted in Figure 1. Panel A illustrates the possibility that the two lipid domains of cardiolipin (CL) molecule can be either in a 'closed' form, when the phosphates are negatively charged, in one leaflet (probably the periplasmic one 29,30 ) of the IMM, with the two hydrophobic domains close together, consistent with what reported for complex III analyzed by X-ray diffraction, 31 or in an 'open' conformation when CL accepts H þ , in conditions favouring respiration and ATP synthesis. In the latter case, the central part of CL loses polarity and the two lipid diglyceride residue domains would be redistributed inside the two leaflets of the IMM.…”
Section: A Hmentioning
confidence: 99%